The impact of the Artificial Intelligence Law on European drone regulation - Castellanos Ruiz, Mª José (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The multitude of applications and uses of drones in recent years is a reflection of the importance that this sector has in the economy of different countries and especially Europe. Well, by combining drones and Artificial Intelligence, more complex and therefore higher risk activities can be carried out, among which are autonomous operations, which will make it possible to transport both parcels and people (air taxis). Firstly, the specific European regulation on drones, related to aerial navigation, will be addressed, which has not yet made much progress in this regard, and the modifications it will undergo as a result of the entry into force of the Artificial Intelligence Law. To then study the impact that the Artificial Intelligence Law could have on drones, in case any part of the regulations were applicable to highly automated drones or autonomous drones. To anticipate some relevant aspect of the Artificial Intelligence Law, it is that all unmanned aircraft are considered “high-risk AI systems” regardless of their level of automation, that is, not only highly automated drones or autonomous drones are included within “high-risk AI systems”, but all types of drones.
Keywords: Artificial Intelligence; AI; autonomous drones; unmanned aircrafts; remotely piloted air¬crafts; RPAS; UAS; UAV; UA; regulation; air transport; civil aviation; incidents; accidents; civil liability